PELESTARIAN LINGKUNGAN HIDUP - Susatyo Adhi Pramono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2006)
AbstractÂ Compatibility is a thing that is relative and subjective. Preserves compatibility of environment means preserve ecological balances. Preserve ecological balances means preserve environment in order not to go down in quality, so that harmonious life would always formed.Â Keyword: environmental conservation, ecological balance.